Image, Power and Identity:A Rereading of Luke 20:20–26 from a Visual Rhetoric Perspective - JING, Minhua (Journal of Research for Christianity in China (JRCC), 2022)
The recent “visual turn” in biblical studies emphasizes the rhetorical power of the interplay between images and words in biblical interpretation. This rhetorical perspective stressing the significance of the visual provides us a fresh understanding of Luke 20:20–26, especially of Jesus’s controversial answer to the question: “Is it lawful for us to pay tribute to Caesar or not” (Lc 20:22). This paper argues that by evoking the rhetorical power of the image on a denarius, the Lucan Jesus gave this question an open answer. This kind of answer made his teaching attractive to the widest streams of Jewish communities, at the same time expressed his peaceful and yet critical attitude towards the politics and ideology of the Roman Empire.
Keywords: visual rhetoric, Roman Empire, coinage, tribute to Caesar